A prospective comparison of octyl-2-cyanoacrylate and suture in facial wounds - Anurag Saxena; Manish Dubey; Gaurav K Saha; Devesh Tiwari; Shaily Tyagi; Roseneel A Singh (Wolters Kluwer Medknow Publications, 2023)
The study aimed to evaluate the efficacy of octyl-2-cyanoacrylate as well as sutures as a wound closure material. Whether octyl-2-cyanoacrylate can be used as an alternative to suture in the closure of facial wounds. Out of total of 19 wounds, 11 wounds were closed with sutures and tissue adhesive both, out of rest 8 wounds, 4 wounds were closed using sutures alone and in 4 wounds, closure was done with tissue adhesive alone. Therefore, a total of 15 facial wounds were divided into two groups: Group-I Cases in whom 3-0 Black silk suture was used for closure of the wound and Group-II Cases in whom Dermabond (Octyl-2-Cyanoacrylate) was used for closure of the wound. Results showed that Octyl-2-cyanoacrylate offered the benefit of decreased procedure time with less pain, no need for its removal, and better cosmetic outcome compared to sutures.